Rick and Morty : finals week. - Kibblesmith, Daniel, 1983-; Bogacs, Christof; Black, Jake; Asmus, James; Festante, Jim (Oni Press, an Oni Press Publication, Adult Swim, 2025)
"It's finals week! And each day brings a new school final for which Morty is woefully unprepared: English lit, gender studies, world religion, government, and science. But instead of helping Morty hit the books, Rick drags him on unexpected and unenlightening adventures, including but not limited to: "doing a Sherlock Holmes," getting trapped in a beat-'em-up video game, starting a cargo cult religion, contesting a political convention, and meeting Morty's future self! Will these hands-on experiences aid in Morty's education, or is he doomed to fail his finals?!"--